Diagnostic Performance of Clinical Laboratory Indicators With Sarcopenia: Results From the West China Health and Aging Trend Study - Yin, Mengting; Zhang, He; Liu, Qianhui; Ding, Fei; Deng, Yiping; Hou, Lisha; Wang, Hui; Yue, Jirong; He, Yong (Frontiers in Endocrinology, 2021)
Background Sarcopenia is an age-related and skeletal muscle disorder involving the loss of muscle mass or strength, and physiological function. Although the diagnostic indicators used in the different guidelines are for muscle mass, strength and physical performance, there are currently no uniform diagnostic criteria. Therefore, we aimed to explore the relationship between a series of biomarkers with sarcopenia in southwest China. Methods We included 4302 patients from West China Health and Aging Trend (WCHAT) study. Sarcopenia was defined according to the Asian Working Group for Sarcopenia: 2019 Consensus Update on Sarcopenia Diagnosis and Treatment. Thyroxine、albumin、total protein、prealbumin、albumin to globulin ratio (A/G)、25(OH)VD、fasting insulin、adrenal cortisol、triglyceride、high-density lipoprotein、hemoglobin and aspartate aminotransferase to alanine aminotransferase ratio (AST/ALT) were measured. The receiver operating characteristic curves (ROC) were established to describe the predictive value for sarcopenia and we also used multivariate logistic regression analysis to identify risk factors of the disease. Results In terms of protein state, patients with sarcopenia had a lower value in total protein, albumin, prealbumin, A/G than the control (P<0.001). Patients had a lower value in triglyceride but a higher value in high-density lipoprotein compared with the healthy in the indicators of lipid metabolism (P<0.001). In the aspect of hormone state, patients had lower free triiodothyronine, fasting insulin but higher free tetraiodothyronine and adrenal cortisol than the healthy (P<0.001). The fasting insulin level (AUC=0.686) and the AST/ALT ratio (AUC=0.682) were the best predictors of sarcopenia among biomarkers. The diagnostic performance of fasting insulin combined with the AST/ALT ratio (AUC=0.720) is equal to multiple indicators (AUC=0.742). Conclusion The fasting insulin combined with the AST/ALT ratio exhibits good diagnostic performance for sarcopenia. Keywords sarcopenia·insulin·ALT·AST